2019
DOI: 10.3390/cancers11020145
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling in Brain Cancers: Roles and Therapeutic Targeting

Abstract: Calcium signaling, in addition to its numerous physiological roles, is also implicated in several pathological conditions including cancer. An increasing body of evidence suggest critical roles of calcium signaling in the promotion of different aspects of cancer, including cell proliferation, therapy resistance and metastatic-related processes. In many cases, this is associated with altered expression and/or activity of some calcium channels and pumps. Brain cancers have also been the subject of many of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 98 publications
2
42
0
5
Order By: Relevance
“…To our knowledge, this phenomenon has not been previously reported in BMSCs or other cell types. A possible explanation for this discrepancy is the difference in the differentiation state of BMSCs because the effects of intracellular Ca 2+ on cell proliferation are dependent on cell types [30][31][32][33], and we observed that PMA suppresses the adipogenesis of BMSCs. In other words, high Ca 2+ might enhance the proliferation of BMSCs committed to adipocytes and have little effect on the proliferation of uncommitted BMSCs.…”
Section: Discussionmentioning
confidence: 65%
“…To our knowledge, this phenomenon has not been previously reported in BMSCs or other cell types. A possible explanation for this discrepancy is the difference in the differentiation state of BMSCs because the effects of intracellular Ca 2+ on cell proliferation are dependent on cell types [30][31][32][33], and we observed that PMA suppresses the adipogenesis of BMSCs. In other words, high Ca 2+ might enhance the proliferation of BMSCs committed to adipocytes and have little effect on the proliferation of uncommitted BMSCs.…”
Section: Discussionmentioning
confidence: 65%
“…The altered expression and activity of specific Ca 2+ channels and pumps have been reported in malignant gliomas [28]. Amlodipine, a commonly used antihypertensive drug, was shown to inhibit tumor growth by the inhibition of YAP/TAZ signaling via the hippo pathway, which is involved in tumor malignancy by the activation of store-operated Ca 2+ entry.…”
Section: Calcium Channel Blockermentioning
confidence: 99%
“…Ions channels expressed on glioblastoma cells including various potassium, calcium, sodium, and chloride ion channels are believed to facilitate pathogenesis of glioblastoma 27,[70][71][72] . Although the expressions of numerous ion channels vary among clinical glioma samples 25 , ion channel expression profiles have been suggested to predict survival in glioma patients 73,74 .…”
Section: E Glioblastoma Electrotaxis Is Mediated By Voltage-gated Iomentioning
confidence: 99%
“…VGCCs are known to play important roles in glioma biology such as cell proliferation, apoptosis, and sensitization to ionizing radiation 27,75,76 . VGCCs can be categorized as high voltage activated (HVA) or low voltage activated (LVA) types [77][78][79] .…”
Section: E Glioblastoma Electrotaxis Is Mediated By Voltage-gated Iomentioning
confidence: 99%
See 1 more Smart Citation